The Multilateral Debt Relief Initiative (G-8 Proposal) and Its Implications for the Fund : Further Considerations. (Policy Papers; Policy Paper ;, 2005)
This supplement discusses the financial structure for the implementation of the G-8 debt relief proposal or Multilateral Debt Relief Initiative (MDRI). Implementation of the MDRI will require action by the Executive Board and by contributions to the Subsidy Account of the PRGF Trust. To be in a position to deliver debt relief under the MDRI by the beginning of 2006 will require the early adoption by the Board of a number of decisions. It will also require the timely consent by all contributors to the Subsidy Account of the PRGF Trust to an amendment of the PRGF Trust Instrument that would allow the transfer of a portion of their resources to a new administered account for use in providing MDRI debt relief to HIPCs with incomes above the MDRI threshold.